2010
DOI: 10.1002/eji.201040372
|View full text |Cite
|
Sign up to set email alerts
|

c‐Rel: A pioneer in directing regulatory T‐cell lineage commitment?

Abstract: The transcription factor Foxp3 controls the differentiation and function of Treg, but the molecular mechanisms that regulate Foxp3 transcription remain elusive. In particular, signals and factors that open and remodel the Foxp3 locus and imprint developing Treg with a stable Foxp3 phenotype are largely unknown. Two reports in this issue of the European Journal of Immunology, together with recent reports published elsewhere, demonstrate that a member of the NF-jB family transcription factors, c-Rel, is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 26 publications
3
43
0
1
Order By: Relevance
“…Reductions in Th1 and Th17 responses and the maintenance of Tregs have been reported after exposure to the JAK2 inhibitor TG101348 [26]. FOXP3 expression is regulated by various factors, such as Smad2/3, Runx1, STAT5, c-Rel, and DNA methylation of the CNS2 region in the FOXP3 enhancer [14,[27][28][29][30]. STAT3 binds to a silencer element within the FOXP3 locus and is associated with a reduction in Smad3 binding [20].…”
Section: Discussionmentioning
confidence: 97%
“…Reductions in Th1 and Th17 responses and the maintenance of Tregs have been reported after exposure to the JAK2 inhibitor TG101348 [26]. FOXP3 expression is regulated by various factors, such as Smad2/3, Runx1, STAT5, c-Rel, and DNA methylation of the CNS2 region in the FOXP3 enhancer [14,[27][28][29][30]. STAT3 binds to a silencer element within the FOXP3 locus and is associated with a reduction in Smad3 binding [20].…”
Section: Discussionmentioning
confidence: 97%
“…For example, NF-B activity may be required for the synthesis of enzymes that directly or indirectly modify chromatin, such as histone acetyl-deacetylases, methyltransferases, ubiquitin ligases, or kinases. In this fashion, NF-B may regulate the ability of other transcription factors to gain access to their DNA-binding sites (24,55). Additional MAPK pathway dependence has been described for a limited number of LMP1 TES2-affected RNAs, including IL-8 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have demonstrated the importance of the NF-κB family member c-Rel for thymic Foxp3 induction (7). c-Rel binds directly to the Foxp3 locus, thereby initiating chromatin opening at a newly identified cis-regulatory element (CNS3) (8), concomitantly binding to further enhancer regions and the Foxp3 promoter (9).…”
mentioning
confidence: 99%